Association between C-reactive protein levels in the first 1–3 days post-transplant and allogeneic immune reactions. (February 2017) - Chen, Yao; Huang, Xiao-Jun; Liu, Kai-Yan; Chen, Huan; Chen, Yu-Hong; Zhang, Xiao-Hui; Wang, Yu; Wang, Feng-Rong; Han, Wei; Wang, Jing-Zhi; Yan, Chen-Hua; Xu, Lan-Ping
Aim: The purpose of this study was to determine whether C-reactive protein (CRP) in the first 1–3 days post-transplant could predict allogeneic immune reactions, including engraftment syndrome or acute graft-versus-host disease (GVHD), in pediatric haploidentical stem cell transplantation.Patients & methods: The study population comprised 175 consecutive pediatric patients. Receiver operating characteristic analysis was performed to identify the cut-off CRP value.Results: The high-CRP group (≥20.1 mg/l) was associated with an increased occurrence of engraftment syndrome (hazard ratio [HR] = 2.046; p = 0.008), II–IV acute GVHD (HR = 2.203; p = 0.001) and severe GVHD (HR = 6.371; p = 0.004).Conclusion: Our data suggest that higher CRP during the first 1–3 days post-transplant could be a predictor of allogeneic immune reactions.